Heterogeneidade nos deficits de percepção do movimento em perturbações do desenvolvimento: o caso do Autismo e da Síndrome de Williams - Ana Maria Abreu; Scania de Schonen (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2009)
Certain deficits in visual motion sensitivity can be assessed via traditional motion coherence tasks where the subject is prompted to detect a percentage of coherent motion embedded in a background of random moving dots. This technique has enabled researchers to infer a deficit in visual motion coherence detection in people with Autism Spectrum Disorder (ASD) and Williams Syndrome (WS) which has been suggested to account for a deficit in function of the dorsal stream in these two groups. It is possible, that not only motion coherence, but several different visual motion deficits coexist. Moreover, a different pattern of low level motion detection deficits might underlie each of these developmental disorders. Here we investigate six different aspects of motion detection sensitivity in ASD and WS with the aim to verify if different deficit patterns might be generalized to each clinical group. Nine children with ASD, 10 children with WS and 96 Typically Developing (TD) children participated in this study. Six Random Dot Kinematogram tasks were used. Withingroup score patterns were very heterogeneous across tasks for both clinical groups. However, participants with ASD showed consistent deficits in a 'Single Mobile'task and participants with WS showed consistent deficits in a 'Motion Coherence'task. The data are discussed in terms of the dissociations found in the motion detection deficit patterns, possibly related with complex co-morbid visual-attention disorders.